rpoB, a promising marker for analyzing the diversity of bacterial communities by amplicon sequencing - Ogier, Jean-Claude; Pagès, Sylvie; Galan, Maxime; Barret, Matthieu; Gaudriault, Sophie (BMC microbiology, 2019)
Microbiome composition is frequently studied by the amplification and high-throughput sequencing of specific molecular markers (metabarcoding). Various hypervariable regions of the 16S rRNA gene are classically used to estimate bacterial diversity, but other universal bacterial markers with a finer taxonomic resolution could be employed. We compared specificity and sensitivity between a portion of the rpoB gene and the V3 V4 hypervariable region of the 16S rRNA gene. We first designed universal primers for rpoB suitable for use with Illumina sequencing-based technology and constructed a reference rpoB database of 45,000 sequences. The rpoB and V3 V4 markers were amplified and sequenced from (i) a mock community of 19 bacterial strains from both Gram-negative and Gram-positive lineages; (ii) bacterial assemblages associated with entomopathogenic nematodes. In metabarcoding analyses of mock communities with two analytical pipelines (FROGS and DADA2), the estimated diversity captured with the rpoB marker resembled the expected composition of these mock communities more closely than that captured with V3 V4. The rpoB marker had a higher level of taxonomic affiliation, a higher sensitivity (detection of all the species present in the mock communities), and a higher specificity (low rates of spurious OTU detection) than V3 V4. We compared the performance of the rpoB and V3 V4 markers in an animal ecosystem model, the infective juveniles of the entomopathogenic nematode Steinernema glaseri carrying the symbiotic bacteria Xenorhabdus poinarii. Both markers showed the bacterial community associated with this nematode to be of low diversity (< 50 OTUs), but only rpoB reliably detected the symbiotic bacterium X. poinarii. Our results confirm that different microbiota composition data may be obtained with different markers. We found that rpoB was a highly appropriate marker for assessing the taxonomic structure of mock communities and the nematode microbiota. Further studies on other ecosystems should be considered to evaluate the universal usefulness of the rpoB marker. Our data highlight two crucial elements that should be taken into account to ensure more reliable and accurate descriptions of microbial diversity in high-throughput amplicon sequencing analyses: i) the need to include mock communities as controls; ii) the advantages of using a multigenic approach including at least one housekeeping gene (rpoB is a good candidate) and one variable region of the 16S rRNA gene. This study will be useful to the growing scientific community describing bacterial communities by metabarcoding in diverse ecosystems.